The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s11104-005-3504-9
|View full text |Cite
|
Sign up to set email alerts
|

Goethite Dissolution in the Presence of Phytosiderophores: Rates, Mechanisms, and the Synergistic Effect of Oxalate

Abstract: The purpose of this study was the elucidation of the chemical mechanism of an important process in iron acquisition by graminaceous plants: the dissolution of iron oxides in the presence of phytosiderophores. We were particularly interested in the effects of diurnal root exudation of phytosiderophores and of the presence of other organic ligands in the rhizosphere of graminaceous plants on the dissolution mechanism. Phytosiderophores of the type 2¢-deoxymugineic acid (DMA) were purified from the root exudates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 60 publications
(62 reference statements)
2
68
2
1
Order By: Relevance
“…3B). Such a result is not unexpected, since it has been reported that more complete dissolution of iron oxide deposits in siderophore-based desorption efforts involves contributions from small-molecule reductants (39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 71%
“…3B). Such a result is not unexpected, since it has been reported that more complete dissolution of iron oxide deposits in siderophore-based desorption efforts involves contributions from small-molecule reductants (39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 71%
“…Thermodynamically, siderophores are very capable of dissolving Fe(III) (hydr)oxides; however, the rate of in vitro dissolution is much slower than the in vivo microbial Fe uptake rate (5)(6)(7). In the presence of a reducing agent, siderophores have been shown to dissolve Fe(III) (hydr)oxides at a faster rate (1,9,12). This increased dissolution resulting from a combined effect of siderophore and reductant could potentially be the mechanism that suffices for the microbial demand for Fe (7).…”
mentioning
confidence: 99%
“…Compared to microbial siderophores, even fewer kinetic data are available for plantborne organic ligands. However, Reichard et al (2005) studied the kinetics of dissolution of a ubiquitous Fe oxyhydroxide, goethite, in the presence of phytosiderophores and oxalate. In doing so, they were able to elucidate the role of these ligands, especially phytosiderophores that are unique to grasses, in the mobilization of Fe from goethite surfaces.…”
Section: Kinetics Of Metals Dynamics In the Rhizospherementioning
confidence: 99%
“…In comparison, this has been much less documented for metal cations, especially heavy metals (Rengel, 2002). A substantial proportion of recent research in this field has been dedicated to elucidating the implications of microbial and plant siderophores in the dissolution of Fe oxides (Inoue et al, 1993;Kraemer et al, 1999;Kraemer, 2004;Reichard et al, 2005). These have shown that such Fe-complexing compounds can efficiently dissolve Fe from poorly soluble Fe oxides, including goethite, which is a ubiquitous crystalline oxyhydroxide in soils.…”
Section: Impact Of Organic Substances On the Speciation Of Trace Elemmentioning
confidence: 99%
See 1 more Smart Citation